Design of a feature recognition system for CAD/CAM integration - Tan, Chee Fai; Kher, Vee Kiat; Ismail, Napsiah (IDOSI Publications, 2013)
This paper presents a methodology for implementing the feature recognition system for achieving the Computer Aided Design/Computer Aided Manufacturing (CAD/CAM) integration goals. The Feature-based modeling is being used to model the solid models. The features being considered in this paper is hole form feature. The input of the feature recognition system is the Standard for the Exchange of Product Model Data (STEP) files. The set of feature recognition rules is generated by using ruled based technique.